AKTIVITAS ANTI BAKTERI KITOSAN DARI CANGKANG KERANG SIMPING PADA KONDISI LINGKUNGAN YANG BERBEDA : KAJIAN PEMANFAATAN LIMBAH KERANG SIMPING (Amusium sp.) - Sulistiyoningrum, Rina Setyowati; Suprijanto, Jusup; Sabdono, Agus (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Waste is one of the major problems in various countries in the world, one of which is the waste of marine products, for example clam shells. This waste can be processed into chitin and chitosan. Chitosan alone has a lot of benefits that have relatively high economic value, such as chitosan as a natural source antibacterial that can be effectively produced. Deacetylation degree of chitosan determined by using data from FTIR spectra and the value was 69.11349%. The results showed that there were soluble chitosan with 1% acetic acid. In the antibacterial test of chitosan on E. coli and S. aureus showed inhibition zone on agar medium. Chitosan provided large inhibition zones on 0.01 Î¼g/disk and 0.02 Î¼g/disk concentrations , however conditions factor of the media effected the growth of those bacteria. Bacteria E. coli bacterium was more sensitive to salinity than thah of S. aureus, while the S. aureus bacterium is more sensitive to pH than that of E. coli bacterium.